Distributional effects of the high school degree in Germany - Johannes Gernandt; Michael Maier; Friedhelm Pfeiffer; Julie Rat-Wirtzler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper investigates the impact of a high school degree on the wage distribution in the period from 1984 to 2004 in Germany. In that period the share of male workers with a high school degree increased from 16 to 25 percent. An econometric evaluation estimator is used to analyze quantile treatment effects for the whole population of male workers and for the subpopulation of workers with a high school degree. It turns out that the impact of a high school degree on the wage distribution for all workers is positive, whereas its impact on the wage distribution of the workers with a high school degree does statistically not differ from zero. This suggests that the selection of students into grammer schools might have been too restrictive. For more workers higher education would have raised their productivity and wages.
Keywords: C21; C14; J31; 330; Economic returns to secondary education; econometric evaluation; quantile treatment effects; educational expansion